Edugame Sejarah Islam pada Masa Pemerintahan Khulafaurrasyidin Berbasis Multi Platform - Sari, Binar Kurnia, Endah Sudarmilah, S.T., M.Eng (2016)
This time, history of Islam at the Khulafaurrasyidin government period has been learned at 5th grade of Madrasah Ibtidayah Muhammadiyah (elementary school). Like the other history lesson, the material of the history of khulafaurrasyidin consisted of many substance and still delivered conventionaly, so sometime makes the student feel bored. Because of it, this research destiny is to make the history of khulafaurrasyidin will be more interesting and more easy to learn for student, that is using educational game which can played on desktop and mobile. This game education served on form visual 2D which made by Construct 2 for game engine and using SDLC (System Development Life Cycle) method Waterfall model. This educational game has been design become 4 main part, that is Abu Bakar ash- Shiddiq, Umar bin Khaththab, Utsman bin Affan and Ali bin Abi Thalib. Every part will game play instruction, game, material, and quiz. According to the writer research on 3 Islamic elementary schools and 2 Islamic junior high school to the student who already learn or not learn yet the history of Khulafaurrasyidin, as much as 89% of student agree if this game education makes the History of Khulafaurrasyidin be more interesting and easy to learn. Keywords : Construct 2, Edugame, History, Khulafaurrasyidin, Multi Platform.